Pitfalls in diagnosis and management of suspected urinary tract infection in an urban tropical primary care setting - Jackson, Alison Ashe; Lai, Pauline Siew Mei; Alias, Aqtab Mazhar; Atiya, Nadia; Ramdzan, Siti Nurkamilla; Abdul Malik, Tun Firzara; Mydin, Fadzilah Hanum Mohd; Abdul Hadi, Haireen; Othman, Sajaratulnisah (Journal of Infection in Developing Countries, 2019)
Introduction: Diagnosis and management of urinary tract infection (UTI) are complex, and do not always follow guidelines. The aim of this study was to determine adherence to the 2014 Malaysian Ministry of Health guidelines for managing suspected UTI in a Malaysian primary care setting. Methodology: We retrospectively reviewed computerized medical records of adults with suspected UTI between July-December 2016. Excluded were consultations misclassified by the search engine, duplicated records of the same patient, consultations for follow-up of suspected UTI, patients who were pregnant, catheterised, or who had a renal transplant. Records were reviewed by two primary care physicians and a clinical microbiologist. Results: From 852 records, 366 consultations were a fresh episode of possible UTI. Most subjects were female (78.2%) with median age of 61.5 years. The major co-morbidities were hypertension (37.1%), prostatic enlargement in males (35.5%) and impaired renal function (31.1%). Symptoms were reported in 349 (95.4%) consultations. Antibiotics were prescribed in 307 (83.9%) consultations, which was appropriate in 227/307 (73.9%), where the subject had at least one symptom, and leucocytes were raised in urine full examination and microscopic examination (UFEME). In 73 (23.8%) consultations antibiotics were prescribed inappropriately, as the subjects were asymptomatic (14,4.6%), urine was clear (17,5.5%), or UFEME did not show raised leucocytes (42,13.7%). In 7 (2.3%) consultations appropriateness of antibiotics could not be determined as UFEME was not available. Conclusion: Several pitfalls contributed to suboptimal adherence to guidelines for diagnosis and management of suspected UTI. This illustrates the complexity of managing suspected UTI in older subjects with multiple co-morbidities. © 2019 Jackson et al.